The Effect of Motivation, Work Environment and Discipline on Employee Productivity - Fajar Purwanto (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
Human resources in the company need to be managed properlyprofessional in order to realize a balance between the needs of employees with the demands and capabilities of the company's organization. Increased productivity can be realized, if the leadership of the company correctly understands the determining factors for the success of increasing work productivity. Because every employee has the right to get fair appreciation from their leaders as a reciprocal of the services provided, so that it can encourage employees to be more motivated in their work.Work. The purpose of this study is to determine the effect of motivation, work environment and discipline simultaneously and partially on the work productivity of Letisia Gallery employees in Jombang. The sample of this research is Letisia Gallery employees in Jombang, with a total sample of 35 respondents. The analysis technique uses Multiple Linear Regression with the or programsoftware SPSS. The results of the study show that simultaneously (simultaneously) it shows that motivation, work environment and discipline have an effect on employee work productivity, partially motivation and work environment have a positive and significant influence on employee work productivity, while partially discipline has no significant effect positive and significant to the work productivity of employees.